Assessing Public Awareness of Circular Economy in Indonesia: Insights from Google Trends Data - Geusan Akbar, Gugun (Lafadz Jaya Publisher, 2024)
This study aims to understand public interest and awareness of the circular economy in Indonesia by analyzing Google Trends search volumes for keywords over the past five years, from 2017 to 2022: